2022
DOI: 10.3389/fimmu.2021.781100
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Robust Protein Associations With COVID-19 Disease Based on Five Clinical Studies

Abstract: Multiple studies have investigated the role of blood circulating proteins in COVID-19 disease using the Olink affinity proteomics platform. However, study inclusion criteria and sample collection conditions varied between studies, leading to sometimes incongruent associations. To identify the most robust protein markers of the disease and the underlying pathways that are relevant under all conditions, it is essential to identify proteins that replicate most widely. Here we combined the Olink proteomics profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Using combinations such as protein cross-linking with MS and computational modeling or affinity purification strategies with SWATH-MS, all integrated in the system biology frame are useful to unravel the networks formed during these host-pathogen interactions too. Recently, multiple proteomic studies identified 13 proteins reproducibly differentially expressed in patients with COVID-19, which were related to cytokine-cytokine interaction, IL18 signaling, fluid shear stress and rheumatoid arthritis, which together validated prior indications of the involvement of cytokine storms in COVID-19 cases ( 88 ).…”
Section: Microorganisms and Their Proteomesmentioning
confidence: 55%
“…Using combinations such as protein cross-linking with MS and computational modeling or affinity purification strategies with SWATH-MS, all integrated in the system biology frame are useful to unravel the networks formed during these host-pathogen interactions too. Recently, multiple proteomic studies identified 13 proteins reproducibly differentially expressed in patients with COVID-19, which were related to cytokine-cytokine interaction, IL18 signaling, fluid shear stress and rheumatoid arthritis, which together validated prior indications of the involvement of cytokine storms in COVID-19 cases ( 88 ).…”
Section: Microorganisms and Their Proteomesmentioning
confidence: 55%
“…These samples may reflect cases with more significant local inflammation, possibly leading to CCL16 induction in non-hepatocytes, or with overproduction by the tumour cells themselves; our HBV-related tumour cohort featuring a lower number of specimens with a single outlier ( Figure 2 ) may actually be sampling the same underlying distribution. Remarkably, a recent survey of five independent proteomics studies in COVID-19 patients revealed a consistent reduction in CCL16 in blood samples [ 71 ]. While the underlying mechanisms have not been investigated, the systemic nature of the disease, potentially involving significant damage to liver tissue [ 72 ], would appear consistent both with reduced synthesis in hepatocytes and with enhanced turnover in the periphery.…”
Section: Resultsmentioning
confidence: 99%
“…Among the proinflammatory interleukins and chemokines genes analyzed in the present work, IL6 , CXCL10 and CXCL11 showed a differential expression (upregulation) in PBCs of COVID-19 patients on hospital admission relative to controls, the upregulation being proportional to the severity of the disease course for CXCL11 . IL-6, CXCL10 and CXCL11 are among the blood circulating proteins found to be robustly associated with COVID-19 disease through a non-biased proteomics approach based on five clinical case-control studies [ 56 ]. Upregulations of IL-6 [ 43 ] and chemokine CXCL10 [ 55 , 57 ] signaling are key components of the SARS-CoV-2 induced cytokine storm.…”
Section: Discussionmentioning
confidence: 99%